The Use of Instagram to Increase the Outcome in Learning the Reaction Rate in Chemistry Subject - Gunawan Fajri; Ibnu Khaldun; Evendi Evendi (Jurnal Penelitian Pendidikan IPA, 2023)
The reaction rate is one of the abstract chemical materials so it requires visualization that can describe the reaction rate events in a more realistic way so that it is more easily understood by students. Visualization can help students be able to observe the symptoms that occur, collect data and draw conclusions from the videos or images presented and improve student learning outcomes. Social media such as Instagram is very possible to be applied in the chemistry learning process which requires visualization to explain some chemistry concepts like reaction rate. The use of Instagram can help students observe the symptoms that occur in the reaction rate through the videos or images presented. Instagram is considered very appropriate to be used to convey learning material that requires visualization to increase students' understanding. The research method used was quasi-experimental with the use of experimental class and control class and shaped Posttest-Only Design. Based on the results of the study, the learning outcomes in the cognitive domain average value of the experimental class was 80.83 and the average value of the control class was 73.83 with increased learning outcomes N-gain of 0.26. Assessment of learning outcomes in the affective and psychomotor domains with the use of final score on a scale of 1 to 4. Calculation of the final score uses the score comparison formula obtained with the maximum score multiplied by the maximum score. In the present study, a final score with an average affective and psychomotor score of 3.21 and 3.04 was obtained respectively.